Early‐life residential exposure to moisture damage is associated with persistent wheezing in a Finnish birth cohort. Issue 10 (11th October 2022) - Tischer, Christina; Täubel, Martin; Kirjavainen, Pirkka V.; Depner, Martin; Hyvärinen, Anne; Piippo‐Savolainen, Eija; Pekkanen, Juha; Karvonen, Anne M.
Abstract: Background and Aims: Moisture damage increases the risk for respiratory disorders in childhood. Our aim was to determine whether early age residential exposure to inspector‐observed moisture damage or mold is associated with different wheezing phenotypes later in childhood. Methods: Building inspections were performed by civil engineers, in a standardized manner, in the children's homes—mostly single family and row houses ( N = 344)—in the first year of life. The children were followed up with repeated questionnaires until the age of 6 years and wheezing phenotypes—never/infrequent, transient, intermediate, late onset, and persistent—were defined using latent class analyses. The multinomial logistic regression model was used for statistical analysis. Results: A total of 63% ( n = 218) had infrequent or no wheeze, 23% ( n = 80) had transient and 9.6% ( n = 21) had a persistent wheeze. Due to the low prevalence, results for intermediate (3.8%, n = 13) and late‐onset wheeze (3.5%, n = 12) were not further evaluated. Most consistent associations were observed with the persistent wheeze phenotype with an adjusted odds ratio (95% confidence intervals) 2.04 (0.67–6.18) for minor moisture damage with or without mold spots (present in 23.8% of homes) and 3.68 (1.04–13.05) for major damage or any moisture damage with visible mold in a child's main living areas (present in 13.4% of homes). Early‐age moisture damage or mold in the kitchen was associated with transient wheezing. Conclusion: At an early age, residential exposure to moisture damage or mold, can be dose‐dependently associated especially with persistent wheezing phenotype later in childhood.